Italian Association of Clinical Endocrinologists (AME) and International Chapter of Clinical Endocrinology (ICCE). Position statement for clinical practice: prolactin-secreting tumors. Issue 3 (3rd February 2022) - Cozzi, Renato; Ambrosio, Maria Rosaria; Attanasio, Roberto; Battista, Claudia; Bozzao, Alessandro; Caputo, Marco; Ciccarelli, Enrica; De Marinis, Laura; De Menis, Ernesto; Faustini Fustini, Marco; Grimaldi, Franco; Lania, Andrea; et al.
Abstract: Prolactinomas are the most frequent pituitary adenomas. Prolactinoma may occur in different clinical settings and always require an individually tailored approach. This is the reason why a panel of Italian neuroendocrine experts was charged with the task to provide indications for the diagnostic and therapeutic approaches that can be easily applied in different contexts. The document provides 15 recommendations for diagnosis and 54 recommendations for treatment, issued according to the GRADE system. The level of agreement among panel members was formally evaluated by RAND-UCLA methodology. In the last century, prolactinomas represented the paradigm of pituitary tumors for which the development of highly effective drugs obtained the best results, allowing to avoid neurosurgery in most cases. The impressive improvement of neurosurgical endoscopic techniques allows a far better definition of the tumoral tissue during surgery and the remission of endocrine symptoms in many patients with pituitary tumors. Consequently, this refinement of neurosurgery is changing the therapeutic strategy in prolactinomas, allowing the definitive cure of some patients with permanent discontinuation of medical therapy.